Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being. This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model. It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Number: 2
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

Plagiarism as a social contract, a new way to approach plagiarism - Gregory, Jess L. (Journal of Academic Ethics, 2021)
Most cases of plagiarism involve a power differential where not every person has the same ability to enter into a social contract. A social contract requires that each party understands the expectations or norms of the contract, has a voice in setting or changing the norms and has the ability to exit the contract. If those with less power want to gain power then they have to engage in activities bound by norms set by others with little or no ability to exit and no voice. Even if one determines that it is an option to choose a role that requires academic writing, even at the earliest grades, then the social contract demands a shared norm of what constitutes correct behavior. This study reviewed the abstracts of articles indexed in Google Scholar from 1999–2019 through the lens of integrative social contract theory (ISCT) and found, in the case of plagiarism, an existing consensus of correct behavior does not exist. Recommendations for establishing a social contract conclude the article.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103650269
Keywords: dept.edl; peer-reviewed

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
1 citations (Crossref) [2023-10-31]
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection